2016
DOI: 10.1039/c6ta01676f
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of an organic acid phase changing material into metal–organic frameworks and the study of its thermal properties

Abstract: A facile solution impregnation method to access a novel type of shape-stabilized PCM employing metal–organic frameworks as the matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 154 publications
(41 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…The comparison of the thermal properties of octadecane@Cr‐MIL‐101‐6C FSPCM in the present study with those of recently reported form‐stable composites is shown in Figure d and Table S8 (Supporting Information) . It can be seen that compared to other octadecane‐based FSPCMs (Table S8, entries 1–4, Supporting Information), the octadecane@Cr‐MIL‐101‐6C FSPCM has higher melting enthalpy (Table S8, entry 5, Supporting Information).…”
supporting
confidence: 54%
“…The comparison of the thermal properties of octadecane@Cr‐MIL‐101‐6C FSPCM in the present study with those of recently reported form‐stable composites is shown in Figure d and Table S8 (Supporting Information) . It can be seen that compared to other octadecane‐based FSPCMs (Table S8, entries 1–4, Supporting Information), the octadecane@Cr‐MIL‐101‐6C FSPCM has higher melting enthalpy (Table S8, entry 5, Supporting Information).…”
supporting
confidence: 54%
“…Among the numerous methods for TES, the application of phase change materials (PCMs) has become a research hotspot because PCMs show high latent heat during phase transition . However, classical solid–liquid PCMs, such as fatty acid, fatty alcohol, fatty hydrocarbon, paraffin, and polyethylene glycol (PEG), are made disadvantageous by the issue of leakage. To solve the leakage problem, many studies have proposed various methods, including the microcapsule method, graft copolymerization, and polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…Routes for encapsulation cover a wide range of techniques such as connement to core-shell polymer architectures, 12 infusion into 3D porous frameworks, [13][14][15] and aided diffusion into carbon nanotubes, 16 nanobers, 17 and metal-organic frameworks (MOFs). [18][19][20][21][22][23] Owing to enhanced surface chemical effects at the nanoscale, PCM connement has in many cases been shown to favourably impact thermodynamic properties, offering more efficient heat transfer, suppressing supercooling and accommodating volumetric changes. 4,19 Connement can also involve complex, multi-step syntheses and expensive materials like carbon nanotubes that prohibit production at meaningful scale.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Owing to enhanced surface chemical effects at the nanoscale, PCM connement has in many cases been shown to favourably impact thermodynamic properties, offering more efficient heat transfer, suppressing supercooling and accommodating volumetric changes. 4,19 Connement can also involve complex, multi-step syntheses and expensive materials like carbon nanotubes that prohibit production at meaningful scale. As such, materials with a high degree of nanoporosity, like MOFs for example, are one of the few candidates that offer true, three-dimensional nanoconnement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation